Pengabdian Kepada Masyarakat (PKM) Peningkatan Kualitas Rumah Swadaya Desa Guntung Ujung - Elva Shanty Widuri; * Arifin; * Fitriansyah; Ahmad Riduan; * Misnawati; Trie Rezky Novianti; Vanness Jan Ho Antony Djong (Jurnal Pengabdian Kepada Masyarakat Multi Disiplin, 2026)
The Community Service Program (PkM) represents a tangible contribution of universities in supporting sustainable development at the local level. Guntung Ujung Village, which possesses considerable human and social resource potential, still faces challenges related to the quality of housing. Self-help houses built independently by residents often do not meet standards of comfort, health, and safety, thereby affecting the quality of life of the families who inhabit them. Through this PkM activity, efforts are made to improve the quality of self-help housing using a community empowerment approach. The program not only emphasizes the physical aspects of buildings but also enhances residents’ knowledge, skills, and awareness regarding the importance of decent housing. By actively involving the community, a sense of ownership and sustainability in maintaining housing quality is expected to emerge. Furthermore, this activity aligns with government agendas in supporting public housing programs, particularly the improvement of self-help houses. The collaborative approach between academics, village government, and the community is expected to produce solutions that are applicable, efficient, and tailored to local needs. Thus, this PkM is not merely a technical intervention but also a process of empowerment that strengthens the capacity of Guntung Ujung Village residents to realize a healthier, safer, and more dignified living environment.